Strategi Pelestarian Cagar Budaya - Nugraha, Yudha Eka; Tadua, Mely Hasni (JURNAL DESTINASI PARIWISATA, 2021)
The Protestant Church of Kupang City (GPKK) is one of the cultural heritages established by the Ministerial Decree NoKM.51 / OT.007 / MKP / 2004. This church was founded in 1614, at that time it was located inside the Fort Concordia (TNI Fortress Dormitory). The cultural heritage of this building category is the potential of Kupang City as a cultural heritage from the Dutch colonial. However, over time, development around the cultural heritage area is getting faster. Many old buildings with historical value are starting to be abandoned or rebuilt into new buildings. Even though historical buildings, especially cultural heritage, are important assets of the state to maintain the historical value of the nation in order to remain sustainable. The objectives of this study are (1) Describe the latest condition of the cultural heritage site of the Protestant Church in Kupang City, (2) Describe the use of cultural heritage sites as tourist attractions, and (3) Recommend strategies for preserving cultural heritage to the authorities. This research uses descriptive qualitative method. The data collected were obtained from field observations, in-depth interviews, documentation, and literature studies related to the preservation of cultural heritage. The results of this study indicate that (1) GPKK as a cultural heritage that has historical value has been managed by the Cultural Heritage Conservation Center (BPCB) for the Bali, NTB and NTT areas since 2004. All Dutch heritage in the GPKK is an important part. from the preservation of the GPKK Cultural Heritage as a cultural tourist attraction. The problems in preservation and management seen in the GPKK arise due to the lack of attention from the Congregation, Church Managers, and the Government in the maintenance of heritage objects. (2) Currently, GPKK is still actively used as a place of worship for the Kupang City congregation. (3) The government is currently in the process of increasing public awareness to protect the site as a cultural heritage of Kupang City. This effort is in order to optimize the use and care factors around the cultural heritage so that it remains sustainable. Keyword: Site Preservation, Cultural Heritage, Protestant Church in Kupang City, Cultural Heritage